A decision support system for waste heat recovery and energy efficiency improvement in data centres. (15th September 2019) - Luo, Yang; Andresen, John; Clarke, Henry; Rajendra, Matthew; Maroto-Valer, Mercedes
Highlights: Data centre sector is fast expanding and energy efficiency can be improved. A systematic approach to waste heat recovery within data centres is proposed. The applicability of the four stages framework is demonstrated through a case study. The decision support system delivers a streamlined and optimised heat recovery strategy. Abstract: Data centre sector is emerging as one of the largest and fastest growing industrial sectors, accounting for 3% of the global electricity supply and contributing to 4% of total greenhouse gas emissions. A framework for waste heat energy recovery and its accompanying decision support system is presented with the ability to evaluate the waste heat (source) and potential demand (sink) compatibility, perform exergy and temporal availability analysis, and undertake cost-benefits and environmental impact analysis of available heat recovery technologies. This four stages framework is implemented through the case study of a medium-sized commercial data centre to provide evidence of its applicability. The results demonstrated that the framework and decision support system can deliver a streamlined and optimised heat recovery strategy for reducing overall energy requirement in the data centre. About 68% of the inevitable waste heat from IT equipment can be recovered by the recommended solution, allowing the recovered waste heat in the form of warm water to be fed back into the facility for applications such as space heating, achieving about 10% improvement in data centre power usage effectiveness. The solutions given by the decision support system are generally accessible for most data centres as the technologies are readily available and often lead to short payback time and substantial energy savings.